23 Doroczna Wystawa - Jakubowski, Krzysztof (1946- ). (Gdańsk : [wydawca nieznany], 1976)
Plakat wystawy, która miała miejsce w Klubie MPiK w Gdańsku w lutym 1976 r. Na druku drzewo i postać.
Keywords: Plakaty -- 1970-2000.